2021
DOI: 10.1183/23120541.00597-2021
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of interstitial lung diseases and their progressive-fibrosing behaviour in six European countries

Abstract: The PERSEIDS study aimed to estimate incidence/prevalence of interstitial lung diseases (ILDs), fibrosing Interstitial lung diseases (F-ILDs), idiopathic pulmonary fibrosis (IPF), systemic sclerosis-associated ILD (SSc-ILD), other non-IPF F-ILDs and their progressive-fibrosing (PF) forms in six European countries, as current data are scarce.This retrospective, two-phase study used aggregate data (2014–2018). In Phase 1, incident/prevalent cases of ILDs above were identified from clinical databases through an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…Hypersensitivity pneumonitis showed the highest percentage of progressive behaviour. Incidence of PF-ILDs ranged between 2.1 and 14.5/10 5 person-years, and prevalence between 6.9 and 78.0/10 5 persons [19].…”
Section: Epidemiologymentioning
confidence: 99%
“…Hypersensitivity pneumonitis showed the highest percentage of progressive behaviour. Incidence of PF-ILDs ranged between 2.1 and 14.5/10 5 person-years, and prevalence between 6.9 and 78.0/10 5 persons [19].…”
Section: Epidemiologymentioning
confidence: 99%
“…Nearly 50% of RA-ILD patients showed a PF-ILD phenotype in the present study. This percentage is higher than in the PERSEID study, a large European retrospective study, demonstrating a progressive pattern in 38% of RA-ILD patients (13). We believe that screening PF-ILD patients is of potential interest for the therapeutic management of RA-ILD patients.…”
Section: Discussionmentioning
confidence: 58%
“…It typically develops in the fifth or sixth decade and can be diagnosed up to 10 years after RA but sometimes occurs before joint symptoms (4,(9)(10)(11)(12). According to the PERSEIDS study, it's prevalence in Europe ranges from 1 to 18.1 per 10 5 persons and among all subtypes of ILDs that are non-idiopathic pulmonary fibrosis (IPF), RA-ILD had the highest incidence in Belgium in 2018 (13).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, because only patients diagnosed with IPF were included in this study, this result could not be applied to patients with progressive pulmonary fibrosis with other ILD subtypes. Because recently published studies suggested operational definition of progressive pulmonary fibrosis with other ILD subtypes, it can be possible to investigate the prevalence of comorbidities in progressive pulmonary fibrosis patients with other ILD subtypes by using nationwide claim data [ 51 , 52 ]. Finally, because this study was a nationwide population-based study based on health claims data, we could only determine the associations between variables, rather than causal relationships.…”
Section: Discussionmentioning
confidence: 99%